The involvement concept—replaceable or irreplaceable? A case for a conceptual analysis of a core concept of media psychological communication research - Schramm, Holger; Olbermann, Zoe; Mayer, Fabian (Frontiers in Psychology, 2024)
The concept of involvement has enriched media psychological communication studies for more than three quarters of a century. The original concept of Sherif and colleagues—the so-called ego-involvement—has been extended piece by piece by various researchers over the decades, so that already in the 1980s voices were raised questioning the usefulness of such a broad meta-concept. In this article, we try to answer the question whether the involvement concept has become obsolete in the meantime by taking a more differentiated look at three different central understandings of the involvement concept (involvement as ego-involvement, as personal relevance and as mode of reception) and discussing their explanatory value. As a result, we conclude that the original conception still has its raison d’être and that media psychological communication research should take more account of this fact when designing its studies.